Decrease of Salivary Melatonin Level in Periodontal Disease: A Review Article - Gofur, Nanda Rachmad Putra; Gofur, Aisyah Rachmadani Putri; Gofur, Rizki Nur Rachman Putra; Kahdina, Mega; Putri, Hernalia Martadila; ., Soesilaningtyas (Jour Med Resh and Health Sci, 2021)
Background: Melatonin is a circulating hormone that is mainly released from the pineal gland. It possesses antioxidant, free-radical scavenging, and immune-enhancing properties. A growing number of studies reveal a complex role for melatonin in influencing various diseases, including periodontal diseases. The purpose of this strudy literature was to knowing the possible relations between salivary melatonin levels and periodontal diseases. Objective: the aim of this study is to find the correlation of salivary melatonin level in periodontal disease. Discussion: The mean of salivary melatonin level was significantly lower in patients with periodontitis compared to healthy subjects. Salivary melatonin concentration decreased in periodontitis patients. Based on the results of any study, it can probably be concluded that salivary level of melatonin has an important role in the pathogenesis of periodontal diseases. It is also worth knowing that this factor could probably be used as a pivotal biological marker in the diagnosis and possible treatment of these diseases, although further research is required to validate this hypothesis. Conclusion: The salivary melatonin level can be used as the biological marker in the early diagnosis of periodontal disease.